Evaluation of meningitis surveillance system in rural area, Rwanda - Solange Nyinawabeza; Jean Claude Niyoyita; Emmanuel Nshimiyimana; Jerome Ndayisenga; Angela Umutoni; Caroline Stamatakis (Scientific Reports)
Abstract Bacterial meningitis is a significant public health concern, with over 1.2 million cases reported globally each year. Rwanda is at increased risk of meningitis outbreaks due to its proximity to countries that lie in the meningitis belt. Rwanda has been conducting surveillance and recording meningitis outbreak cases across the country since 2012. We evaluated the meningitis surveillance system at Kibogora Level Two Teaching hospital, Nyamasheke district of Rwanda to assess whether the surveillance objectives were being met. The study was cross-sectional, using purposive sampling to select healthcare providers participating in the meningitis surveillance. Rwanda’s bacterial meningitis data from 2017 to 2021 was collected from clinical registers and Rwanda’s electronic integrated disease surveillance system (eIDSR) from Kibogora Level Two Teaching Hospital catchment area, Nyamasheke district, Rwanda. The study area was chosen because a meningitis outbreak was recorded in the area and its bordering country namely Democratic of Republic of Congo (DRC) prior to the current study period. Information on the participant’s demographics, occupation, training, professional experience, and their perception on the surveillance system were gathered using a structured questionnaire. Meningitis surveillance systems attributes including usefulness, acceptability, and flexibility were assessed and categorized as poor (< 50% score), reasonable (50–69%), good (70–90%), or excellent (> 90%) in reference to the study conducted on the evaluation of the meningitis surveillance system in Luanda Province, Angola in March 2017. Data collected from clinical registers and eIDSR were used to assess core functions of the meningitis surveillance system including accuracy in detection of cases, laboratory confirmation of cases, and availability of evaluation reports. Descriptive statistics were analyzed using Microsoft Office Excel. Thirty-one healthcare providers working on meningitis surveillance in the Kibogora Level Two Teaching Hospital were interviewed. During the period under evaluation, 48 suspected cases of meningitis were identified; 43 (90%) met the surveillance case definition, and only 10 (21%) were reported to eIDSR (completeness). Attributes such as flexibility scored good while stability and acceptability scored reasonable. Out of 48 suspected meningitis cases, only 2 (4%) samples were collected from patients and sent to the hospital laboratory for analysis. This study found a good knowledge level of the meningitis surveillance system among healthcare workers; however, the system’s core functions, such as notification rate and laboratory confirmation were found to have gaps. The notification rate could be improved by conducting regular refresher courses for healthcare workers supporting surveillance system. Moreover, MoH could enhance the implementation of a national policy requiring mandatory CSF sample testing to confirm pathogens for all suspected cases. Future studies should explore performance-based incentives to improve reporting completeness. Rwanda’s experience could provide insights for other low-resource settings facing similar surveillance challenges.